Tourism safety, security and resilience : integrated community-based approaches - Isaac, Rami K.; Maingi, Shem Wambugu; Gowreesunkar, Vanessa G. B. (Milton Park, Abingdon, Oxon ; New York : Routledge, 2025)
"This significant volume critically explores the implications of tourism safety and security and how communities in tourism destinations try to be resilient in the face of these impacts. This book is essential reading for all tourism students, researchers and academic as well as those interested in conflict and crisis recovery"--
Keywords: Tourism -- Security measures; Tourism -- Safety measures; Tourism -- Social aspects; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism